Volume 10, Issue 2 Editorial: Celebrating 10 Years of the Journal of Financial Therapy - Kristy L Archuleta (Journal of Financial Therapy, 2019)
The Financial Therapy Association (FTA) and Journal of Financial Therapy have much to celebrate over the past decade!
Keywords: financial therapy